Robot adoption: evidence from perceived benefits and industry adoption pressure - Mai, Qiang; Zhang, Qi-nan; Zhang, Fanfan; Ji, Fang (Technological and Economic Development of Economy, 2025)
Recent research suggests that many firms have begun to adopt robots to take over tasks that were previously carried out by humans. However, current study still does not seem to explain the possible reasons and behavioral intentions for this robot adoption preference, and some scholars attribute them only to rising hiring costs, which may lead to a misleading impression, as firms adopting robots do not appear to reduce the wages of their workers. In this paper, we conduct examinations using robot data from the Chinese General Administration of Customs and a range of firm characteristics. The result shows that robot adoption willingness of firms depends more on their perceived benefits from robots and the pressure they feel from their peers than on rising employment costs, and that higher-skilled sectors tend to approach robots proactively, whereas lower-skilled sectors tend to be reactive in the robot adoption process. In addition, firms exhibit different behavioral choices when deciding whether to adopt robots, with those that have advantages in terms of firm size and employee capacity more likely to translate their perceived benefits of robots and industry adoption pressures into robot adoption behavior. This work offers a new explanation for the current phenomenon of robot substitution for human labor in Chinese firms and provide new evidence for technology adoption theory.First published online 19 February 2025